The Role of Facebook and Twitter in Social Movements: A Study on the July 15 Coup Attempt in Turkey - Semra Demirdiş (Türkiye İletişim Araştırmaları Dergisi)
There is currently a considerable degree of discussion focusing on the relationship between socialmovements and digital platforms. This paper investigates the role played by several social media platforms(Twitter and Facebook) in the coup attempt in Turkey on July 15th, 2016. It includes an analysis of webcontent to establish ways to understand the usage of social and digital media by Turkish citizens on the July15 coup. The research uses qualitative content analysis, including: (1) an examination of tweets and trendinghashtags on Twitter; and (2) an examination of Facebook pages and groups, including photographs, videosand comments. This study indicates that Twitter and Facebook played a vital role in the resistance of citizensagainst the coup attempt, which was organised by the Gulenist terrorist organisation, through the provisionof effective communication between activists, along with their effective mobilisation and the process ofestablishing a common identity. The study also demonstrates how photographs and videos shared on socialwebsites became positive motivators both during and following the 15th of July coup attempt.